Hollow Composite Structures One-a-minute - Drummer, Dietmar; Müller, Thomas; Hoffmann, Leo; Müller, Norbert (Kunststoffe International, 2011)
The FIT-Hybrid technology permits efficient and flexible production of highstrength hollow structures. The combination of forming and molding offers a high degree of design freedom and high mechanical properties with a simultaneous reduction in the part weight. Its profitability derives from the energy-efficient and automatable production method. The consistent use of thermoplastic materials based on one polymer type also permits inexpensive recycling. The process was awarded the NoAE Innovation Prize for "efficient and flexible production" at the Würzburg Automobilgipfel 2010 [8]. On 29 March the FIT-Hybrid composite is also to receive the IEC Innovation Award in Paris for the method presented.
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-KT.hollow